New solution method for latent energy storage and thermoeconomic optimization for an air conditioning system. (January 2020) - Akbari, A.D.; Talati, F.; Mahmoudi, S.M.S.
Highlights: An air-conditioning system integrated with a LTES is analyzed thermoeconomically. A novel semi-analytical solution method for phase-change process is proposed. The proposed and numerical results are compared with one another. The results obtained from proposed and numerical methods are in good agreement. The performances of the overall system are compared for three types of PCMs. Abstract: An air-conditioning system equipped with a latent thermal energy storage is analyzed thermodynamically and economically. A new solution method is introduced and used to solve the phase change problem. In addition, based on the 2-D modified enthalpy method, a numerical solution is carried out. The numerical results are validated using the existing experimental ones. The results obtained from the proposed method are compared with those of the numerical ones for some effective parameters. A maximum difference of 2.7% is obtained between them. By applying the proposed method, the effects of parameters such as the inlet and outlet air temperatures on the operating parameters including the coefficient of performance, exergy efficiency, total product unit cost, total investment cost, phase change material (PCM) slabs' thickness, and length are investigated. The thermodynamic and economic performances of the overall system are compared for three types of PCMs with identical melting point temperatures, namely; RT27, S27 and PureTemp27. It is shown that the total product unit cost decreases as the air temperature difference in passing through the air-conditioning system increases. This occurs in spite of the increment of investment cost because of the thermal efficiency enhancement. In the proposed method, the desired output can be obtained at any time and location with no need to previous time steps and other discretized points. This improves the optimization process for the system. The results show that, compared to the other PCM types, the PureTemp27 brings about better thermodynamic and thermoeconomic performances for the system.